Reducing Trade Inequality: A Network-Based Assessment - J. Garcia-Algarra; G. Gómez Bengoechea; M. L. Mouronte-López (Complexity)
International trade, the network that underpins globalization, shows an extreme inequality. Despite efforts of multilateral organizations to foster a more fair world through trade agreements, it is hard to assess the effect of these changes on such a complex system. We have measured, using numerical simulation on a recently published network model, the impact of simple policies to boost trade chances among the weakest economies. Results suggest that global inequality may be reduced improving trade among low-income economies.